Analyse variationelle et numerique de quelque problemes de contact entre des corps - Ferhat, Mohammed Said (Universty of Eloued جامعة الشهيد حمة الأخضر, 2023)
الملخص: الهدف من هذه الأطروحة هو النمذجة، والدراسة المتغيرة والرقمية لبعض مشاكل الاتصال مع أو بدون احتكاك، بين جسم مشوه وأساس، أو بين جسمين مشوهين. هنا نأخذ في الاعتبار قوانين السلوك غير الخطية للمواد البلاستيكية المرنة اللزوجة، والمطاطية الكهربية اللزجة، والمواد الكهروضغطية اللزجة المطاطية ذات الذاكرة الطويلة. لهذه المشاكل نحصل على صيغ متغيرة تليها نتائج الوجود والتفرد للحلول الضعيفة. تعتمد التقنيات المستخدمة على نظرية المؤثرات الرتيبة متبوعة بنسخة من نظرية كوشي ليبشيتز وحجج النقطة الثابتة لباناخ. أخيرًا، نقترح تقريبًا عدديًا للمشكلة الميكانيكية البحتة باستخدام مخططات منفصلة ونحصل على نتائج تقدير الخطأ. Résumé : انجلزية The object of this thesis is the modeling, the variational and numerical study of some contact problems with or without friction, between a deformable body and a foundation, or between two deformable bodies. Here we consider nonlinear laws of behavior for elastic-viscoplastic, electro-viscoelastic, and viscoelastic piezoelectric materials with long memory. For these problems we obtain variational formulations followed by existence and uniqueness results of weak solutions. The techniques employed are based on the theory of monotone operators followed by a version of the Cauchy-Lipschitz theorem and Banach's fixed point arguments. Finally, we propose a numerical approximation of the purely mechanical problem using discrete schemes. For these schemes, we obtain error estimation results.
أطروحة دكتوراه تخصص: رياضيات تطبيقية في العلزم الدقيقة
Keywords: عربيّــة: اللدونة المرنة اللزجة، التصاق، تلف، استجابة مخمدة طبيعية، توافق طبيعي، نقطة ثابتة، عناصر محدودة; Electro-viscoplasticity, adhesion, damage, normal damped response, normal compliance, fixed point, finite elements